Diagnosis of pupils' difficulties and errors in learning mathematics at primary school in Ibadan (2001)
This study considers the results of a diagnostic test of pupils’ difficulty and contrast the difference in performance between the lower attaining percentile and the higher percentile. It illustrates a difference in qualitative thinking between those who succeed and those who fail in mathematics. Methods developed by Newman (1977) for analyzing errors made by children attempting verbal arithmetic problems were used. The study then answered some research questions.